Increased Root Canal Endotoxin Levels are Associated with Chronic Apical Periodontitis, Increased Oxidative and Nitrosative Stress, Major Depression, Severity of Depression, and a Lowered Quality of Life - Gomes, Cinthya; Martinho, Frederico Canato [UNESP]; Barbosa, Décio Sabbatini; Antunes, Leonardo Santos; Póvoa, Helvécio Cardoso Corrêa; Baltus, Thiago Hissnauer Leal; Morelli, Nayara Rampazzo; Vargas, Heber Odebrecht; Nunes, Sandra Odebrecht Vargas; Anderson, George; Maes, Michael (Springer Nature, 2018)
Evidence indicates that major depression is accompanied by increased translocation of gut commensal Gram-negative bacteria (leaky gut) and consequent activation of oxidative and nitrosative (O&NS) pathways. This present study examined the associations among chronic apical periodontitis (CAP), root canal endotoxin levels (lipopolysaccharides, LPS), O&NS pathways, depressive symptoms, and quality of life. Measurements included advanced oxidation protein products (AOPP), nitric oxide metabolites (NOx), lipid peroxides (LOOH), −sulfhydryl (SH) groups, total radical trapping antioxidant parameter (TRAP), and paraoxonase (PON)1 activity in participants with CAP, with and without depression, as well as healthy controls (no depression, no CAP). Root canal LPS levels were positively associated with CAP, clinical depression, severity of depression (as measured with the Hamilton Depression Rating Scale (HDRS) and the Beck Depression Inventory) and O&NS biomarkers, especially NOx and TRAP. CAP-related depression was accompanied by increased levels of NOx, LOOH, AOPP, and TRAP. In CAP participants, there was a strong correlation (r = 0.734, p OpenSPiltSPi 0.001) between root canal LPS and the HDRS score. There were significant and positive associations between CAP or root canal endotoxin with the vegetative and physio-somatic symptoms of the HDRS as well as a significant inverse association between root canal endotoxin and quality of life with strong effects on psychological, environmental, and social domains. It is concluded that increased root canal LPS accompanying CAP may cause depression and a lowered quality of life, which may be partly explained by activated O&NS pathways, especially NOx thereby enhancing hypernitrosylation and thus neuroprogressive processes. Dental health and “leaky teeth” may be intimately linked to the etiology and course of depression, while significantly impacting quality of life.
Keywords: Antioxidants; Chronic apical periodontitis; Depression; Endotoxin; Inflammation; LPS; Oxidative and nitrosative stress